Mesopore-dominant porous carbon derived from bio-tars as an electrode material for high-performance supercapacitors - Mi-Mi Wei; Wen-Ping Li; Jie Weng; Yun-Quan Liu; Shui-Rong Li; Yue-Yuan Ye; Meng Wang; Duo Wang (Journal of Saudi Chemical Society, 2019)
For the first time, toxic bio-tars collected from the gasification of pine sawdust are used as the precursor for activated carbons. Various types of activation agents including KOH, K2CO3, H3PO4 and ZnCl2 were screened for obtaining superior activated carbons. When KOH was used as an activation agent, the obtained activated carbons exhibited high specific surface area and large mesopore volume. The activated carbons were further employed to be the electrode material of supercapacitors, and its specific capacitance reached up to 260 F g−1 at 0.25 A g−1 current density. Also, it showed an excellent rate performance from preserving a relatively high specific capacitance of 151 F g−1 at 50 A g−1. The assembled device also exhibited the good electrochemical stability with the capacity retention of 90% after 5000 cycles. Furthermore, the maximum energy density of the activated carbons in organic electrolyte reached 17.8 Wh kg−1. Keywords: Tars, Activated carbon, Potassium hydroxide, Supercapacitors, Gasification